2012
DOI: 10.1038/ncomms2189
|View full text |Cite
|
Sign up to set email alerts
|

Surface symmetry-breaking and strain effects on orbital occupancy in transition metal perovskite epitaxial films

Abstract: The electron occupancy of 3d-orbitals determines the properties of transition metal oxides. This can be achieved, for example, through thin-film heterostructure engineering of ABO 3 oxides, enabling emerging properties at interfaces. Interestingly, epitaxial strain may break the degeneracy of 3d-e g and t 2g orbitals, thus favoring a particular orbital filling with consequences for functional properties. Here we disclose the effects of symmetry breaking at free surfaces of ABO 3 perovskite epitaxial films and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
313
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(343 citation statements)
references
References 31 publications
30
313
0
Order By: Relevance
“…The Mn valence near the interface (small i's) is suppressed due to the large PZT surface charge and gradually returns to nominal valence þ3.3 near the 7th MnO 2 plane. While the simulated surface Mn valence (i ¼ 10) is around 3.3 or larger, the surface is affected by the absence of apical oxygen coordination 25 and should be smaller due to higher 3z 2 -r 2 orbital occupancy than in the bulk.…”
mentioning
confidence: 93%
“…The Mn valence near the interface (small i's) is suppressed due to the large PZT surface charge and gradually returns to nominal valence þ3.3 near the 7th MnO 2 plane. While the simulated surface Mn valence (i ¼ 10) is around 3.3 or larger, the surface is affected by the absence of apical oxygen coordination 25 and should be smaller due to higher 3z 2 -r 2 orbital occupancy than in the bulk.…”
mentioning
confidence: 93%
“…Many of the same classes of correlated oxides are broadly explored for their electrochemical properties, enabling applications from solid oxide fuel cells to oxygen sensors [5][6][7][8] , and suggesting intrinsic links between physical and electrochemical functionalities. While the bulk properties of these materials are now amenable to a broad range of scattering and electron microscopy techniques, detailed studies of the structure and properties of their surfaces have remained challenging [9][10][11][12][13][14] . Understanding the emergent physical phenomena at surfaces requires the capability to probe local composition, recognize minute deviations from ideal structures and explore atomic coupling to electronic properties.…”
mentioning
confidence: 99%
“…In the La 1-x Sr x MnO 3 solid solution, the electron occupancy of the e g doublet depends on the strength of the JahnTeller distortion, which in turn is determined by the hole doping level, x (Tokura and Nagaosa, 2000). In epitaxial thin films, however, similarly to the Jahn-Teller distortion, misfit strains have the ability to break the x 2 − y 2 /3z 2 − r 2 orbital degeneracy (Fang et al, 2000) as recently confirmed by X-ray linear dichroism investigations (Huijben et al, 2008;Tebano et al, 2008;Pesquera et al, 2012). A thorough investigation taking into account the attenuation of the signal with the depth in the sample, suggests that the observed X-ray linear dichroism is rather a consequence of the superposition of interfacial and free surface effects (Pesquera et al, 2012).…”
Section: Misfit Strainmentioning
confidence: 80%
“…In epitaxial thin films, however, similarly to the Jahn-Teller distortion, misfit strains have the ability to break the x 2 − y 2 /3z 2 − r 2 orbital degeneracy (Fang et al, 2000) as recently confirmed by X-ray linear dichroism investigations (Huijben et al, 2008;Tebano et al, 2008;Pesquera et al, 2012). A thorough investigation taking into account the attenuation of the signal with the depth in the sample, suggests that the observed X-ray linear dichroism is rather a consequence of the superposition of interfacial and free surface effects (Pesquera et al, 2012). As shown in Figure 1C, those results suggest that a tensile strain would favor the occupancy of the in-plane x 2 − y 2 orbitals, while a compressive strain would induce the occupancy of the out-of-plane 3z 2 − r 2 ones, as expected from electrostatic arguments.…”
Section: Misfit Strainmentioning
confidence: 86%
See 1 more Smart Citation